Revisiting the Role of Intensive Glucose Control on Cardiovascular Outcomes - Shuman, Jill (MD Conference Express, 2015)
While good glycemic control is associated with preventing microvascular complications, its association with cardiovascular disease is far less straightforward. Key studies have yet to report a consistently positive effect of intensive glucose lowering on cardiovascular outcomes. For now, intensive glucose control should not be considered a strategy to prevent macrovascular complications.